Utilização de biorrealimentação por meio de CO2 expirado na prática de atividade aeróbia para análise de indivíduos obesos e com sobrepeso - Haack, Vanessa Cristina (2014)
This work presents the use of biofeedback as a way to record the ventilatory mechanics of overweight and obese individuals, through the use of a capnometer to measure the CO2 concentration during walking on a treadmill, inducing them to increase the amount of exhaled gas. The aim of this study was to conditioning the mechanical ventilation study group improving their oxygen uptake. Eighteen individuals (12 obese and / or overweight, with 8 women and 4 men and 6 with standard weight for the classification of fat percentage, with 2 women and 4 men) aged 20 to 55 years old were evaluated. Individuals who had been clinically diagnosed with hypertension, diabetes or any disease without any medical control, pregnant women and participants with any type of musculoskeletal or joint problem that made it difficult in gait were excluded. It was initially carried out the measurement of skinfolds in order to separate the respective groups, and the measurement of VO2 through submaximal test on a cycle ergometer at Astrand protocol to verify the initial fitness of the participants. The protocol was performed in 12 sessions in alternate days, where each volunteer was subjected to 15 minutes of continuous aerobic activity on a treadmill. Every 5 minutes a recording was performed with data of the biofeedback and values of capnometer equipment, totaling 15 minutes. A mask that remained attached to capnometer and biofeedback device that returned the information of the execution engine to each participant was used. The treadmill speed was monitored through the oscillation of heart rate, which was maintained at 65% of maximum heart rate (MHR) for age, as measured by frequency counter. The average percentage of fat found in the control group was 17±5.79% and for the study group was 35±4.27%. The average analysis of the CO2 values of the study group was initially 23.18±3.73mmHg and the end of the collections was 27.39±3.03mmHg, and for the control group the average was respectively 20.77±3.86 mmHg and 26.44±3.90mmHg. When comparing obese and/or overweight individuals classified with normal fat percentage and their respective CO2 concentrations there is a statistically significant difference. Capnometer for measuring CO2 through the use of biofeedback as a means of inducing increased flow of exhaled gas during aerobic activity proved to be a useful and applicable tool. It was possible to verify a type of respiratory behavior in obese and overweight and associate measurements obtained by capnometer with the values of respiratory frequency.